Soil chemical properties and growth response of Moringa oleifera to different sources and rates of organic and NPK fertilizers - A. G. Adebayo; H. A. Akintoye; A. O. Shokalu; M. T. Olatunji (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose The need for increasing production of Moringa oleifera in Nigeria can be achieved through adequate fertilization. This study investigated the effects of sources and rates of NPK (15:15:15) and compost on soil properties and productivity of Moringa at National Horticultural Research Institute, Ibadan, Nigeria. Methods NPK was applied at 30, 60, and 90 kg N/ ha, cow dung (CD), poultry manure (PM) and organomineral (OM) were applied at 10, 20 and 30 tons/ha. The experimental design was a randomized complete block design with three replicates. Organic fertilizers were incorporated into the soil 2 weeks before sowing; NPK was split applied at 2 and 5 weeks after sowing. Seeds were sown at 75 cm × 75 cm spacing. Data were taken on plant height (cm), stem girth (cm), number of leaves, leaf biomass, stems weight and post-planting soil properties. Results Growth values for NPK and compost treatments were higher than the control. PM applied at 30 tons ha−1 resulted in highest growth values: plant height (65.91 cm), stem girth (1.51 cm) and number of leaves (14.20). PM applied at 30 tons ha−1 gave higher stem weight (2249.9 g) and leaf biomass (3610.5 g). Post-planting soil analysis indicated that nitrogen, phosphorus, calcium, sodium, manganese, iron and zinc contents were higher in plots with organic and inorganic fertilizers except for potassium and magnesium. Conclusion PM proved more superior to CD manure and others because it produced better growth attributes such as shoot height, stem girth and number of leaves and leaf biomass than its counterparts produced.